Impact of antioxidant supplementations on cardio-renal protection in cardiac surgery: an updated and comprehensive meta-analysis and systematic review - Ali-Hassan-Sayegh, Sadegh; Weymann, Alexander (Cardiovascular therapeutics, 2016)
This systematic review with meta-analysis sought to determine the strength of evidence in terms of the impact of common antioxidant supplementations, such as N-acetylcysteine (NAC), vitamin C, and polyunsaturated fatty acids (PUFA) on perioperative outcomes after cardiac surgery with particular focus on the incidence of atrial fibrillation (AF) and acute kidney injury (AKI) with associated mortality. A total of 29 trials were identified that reported incidence of AF and 17 trials that reported incidence of AKI. Pooled analysis reported that NAC (OR=0.5; P=.001), vitamin C (OR=0.4; P=.001), and PUFA (OR=0.8; P=.01) administration were associated with significantly reduced incidence of AF. In terms of postoperative AKI, only NAC was shown to be a beneficial supplement that was able to significantly reduce the incidence of AKI (OR=0.7; P=.01), and NAC could also significantly decrease overall mortality (OR=0.3; P=.03) following cardiac surgery. The use of NAC in patients undergoing cardiac surgery should be strongly recommended due to its combined cardio-renal protective effects and reduced mortality. Also, PUFA and vitamin C might be able to significantly decrease the incidence of arrhythmia; however, reno-protective effects and impact on overall mortality of these supplements seem to be less impressive.